Economic Evaluation of National Patient Blood Management Clinical Guidelines in Cardiac Surgery - Irving, A.H.; Harris, A.; Petrie, D.; Higgins, A.; Smith, J.A.; Tran, L.; Reid, Christopher; McQuilten, Z.K. (ELSEVIER SCIENCE INC, 2022)
Objectives: To the best of our knowledge, no published clinical guidelines have ever undergone an economic evaluation to determine whether their implementation represented an efficient allocation of resources. Here, we perform an economic evaluation of national clinical guidelines designed to reduce unnecessary blood transfusions before, during, and after surgery published in 2012 by Australia's sole public blood provider, the National Blood Authority (NBA). Methods: We performed a cost analysis from the government perspective, comparing the NBA's cost of implementing their perioperative patient blood management guidelines with the estimated resource savings in the years after publication. The impact on blood products, patient outcomes, and medication use were estimated for cardiac surgeries only using a large national registry. We adopted conservative counterfactual positions over a base-case 3-year time horizon with outcomes predicted from an interrupted time-series model controlling for differences in patient characteristics and hospitals. Results: The estimated indexed cost of implementing the guidelines of A$1.5 million (2018-2019 financial year prices) was outweighed by the predicted blood products resource saving alone of A$5.1 million (95% confidence interval A$1.4 million-A$8.8 million) including savings of A$2.4 million, A$1.6 million, and A$1.2 million from reduced red blood cell, platelet, and fresh frozen plasma use, respectively. Estimated differences in patient outcomes were highly uncertain and estimated differences in medication were financially insignificant. Conclusions: Insofar as they led to a reduction in red blood cell, platelet, and fresh frozen plasma use during cardiac surgery, implementing the perioperative patient blood management guidelines represented an efficient use of the NBA's resources.